Steroid Responsive Mononeuritis Multiplex in the Cronkhite–Canada Syndrome - Lo, Y. L.; Lim, K. H.; Cheng, X. M.; Mesenas, S. (Frontiers in Neurology, 2016)
The Cronkhite–Canada syndrome (CCS) is a rare disorder of unknown origin characterized by generalized gastrointestinal polyposis, alopecia, hyperpigmentation, and onychodystrophy. We report a case of CCS with concomitant presentation of mononeuritis multiplex. The electrophysiological findings and steroid responsiveness suggests presence of an autoimmune mechanism.